Risk factors for preterm birth: a community based longitudinal study in rural Mysuru, Karnataka, India - A., Rashmi; M. R., Narayanamurthy; G. S., Vidya; K., Vidyalaxmi; M., Renuka (International Journal Of Community Medicine And Public Health, 2016)
Background: Preterm birth is defined as birth of the baby before 37th completed week counting from first day of the last menstrual period. Preterm infants constitute two-third of low birth weight babies. Estimated 15 million babies are born too early every year. Almost 1 million children die each year due to complications of preterm birth. Methods: A Community based longitudinal study was conducted for the period of one year (March 2015- February 2016). All the antenatal mothers who completed 24 weeks of gestation, who were available for follow- up till 1week after the delivery were included in the study. Registration of the mothers was done for the period of 6 months, follow up was done till their 1st week of the delivery. During the first visit, a pretested semi structured proforma was administered which includes details regarding socio demographic background, major risk factors etc. Mothers were examined and Information pertaining to basic investigations was collected. Mothers were followed up till the delivery and details regarding delivery and birth weight were collected. Minimum of 3 visits were made before declaring lost follow up. Data collected was entered in MS office excel sheet and analyzed using Statistical Package for Social Sciences(SPSS) software version 22.0. Results: Out of 257 registered mothers, 246 mothers had live birth. 11 mothers lost to follow-up. Total numbers of preterm birth out of 246 deliveries were 5 (2%) 95% CI (0.22-3.78%). Gestational diabetes mellitus, Education of the mother and type of the family was found to be statistically significant (p<0.05) under univariate analysis. Whereas multivariate regression showed that age of the father was the independent predictor of Preterm birth and higher the age of father risk of having preterm baby was 7.57 times higher. Conclusions: Though presence of ‘high risk’ factors are attributed to the adverse pregnancy outcomes like preterm birth, socio demographic characteristics of the antenatal mother and her family play a vital role.